Implementasi Program Uji Kompetensi Bidang Teknis pada Badan Pengembangan Sumber Daya Manusia Provinsi Jawa Timur - Davita Sherin Agustin; Tjitjik Rahaju; Indah Prabawati; Firre An Suprapto (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Competency development for the State Civil Apparatus (ASN) is a crucial element in establishing a professional, transparent, and public service-oriented bureaucracy, in alignment with the implementation of the merit system. The Human Resources Development Agency (BPSDM) of East Java Province conducts a competency assessment program to measure, evaluate, and map the technical capabilities of ASN personnel. However, the implementation of this program faces various challenges, such as a lack of understanding among ASN regarding the purpose of the assessment, a limited number of assessors, and a mismatch between the budget and the number of participants. This study aims to provide a comprehensive description of the implementation of the Technical Competency Assessment program at the BPSDM of East Java Province.This study employs a qualitative approach of a descriptive nature. The research focus is analyzed using George C. Edwards III’s policy implementation theory, which encompasses four key variables: communication, resources, disposition, and bureaucratic structure. Data were collected through observation, in-depth interviews, and documentation. The data analysis technique follows the Miles and Huberman model, comprising data reduction, data display, and conclusion drawing. Research findings indicate that regarding the Communication variable, the process of transmitting information and scheduling instructions from the organizing committee was well-structured, despite delays in regional agencies receiving official circulars; in terms of clarity, participants well understood the program's general essence and benefits, although some candidates felt the detailed material and technical guidelines remained somewhat generic.